A contribution to the knowledge of the taxonomy of the subgenus Abrothrix (Angelomys) (Rodentia, Cricetidae) in southernmost South America - Sánchez, Julieta; Poljak, Sebastián; Teta, Pablo Vicente; Lanusse, Lucas; Lizarralde, Marta Susana (Polar Biology)
As currently understood, the subgenus Abrothrix (Angelomys) Teta et al. (33:153–182, 2017) includes four species of small (< 25 g), short-tailed mice (< 65% of the length of the head plus body), widely distributed from southern Peru to southernmost Argentina and Chile. At least four nominal forms of this subgenus (i.e., canescens Waterhouse 2:109–27, 1837, hershkovitzi Patterson et al. (23:1–16, 1984), llanoi Pine (40:63–68, 1976), and xanthorhina Waterhouse 2:109–27, 1837), reach the southernmost portion of South America, being their taxonomy largely discussed during the last century. In this contribution we reviewed all these nominal forms, which were alternatively considered as valid at the species level or as subspecies of A. olivacea, (Waterhouse 2:109–27, 1837) based both on molecular (D-loop) and morphological (qualitative and quantitative) evidence. Phylogenetic and phylogeographic analysis of molecular data depicts a main break between north (= olivacea) and south (= xanthorhina) population of the Magellan Strait, which is moderately reflected in multivariate analysis of morphological cranial traits. Based on these results, the lack of qualitative craniodental differences among samples, plus additional genetic evidences (SNPs), we discuss some alternative taxonomic scenarios (i.e., if xanthorhina is a valid species or a subspecies of olivacea). Within this context, we advocated for the recognition at the subspecies level of the nominal forms hershkovitzi and llanoi, based on their large phenotypic distinctiveness and geographical isolation. We consider these data to be of utmost importance for the conservation of the biodiversity of the delicate island ecosystems of southernmost South America. Fil: Sánchez, Julieta. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: ...